Impact of age and sex on left ventricular function determined by coronary computed tomographic angiography: results from the prospective multicentre CONFIRM study - Gebhard, Catherine; Buechel, Ronny R.; Stahli, Barbara E.; Gransar, Heidi; Achenbach, Stephan; Berman, Daniel S.; Budoff, Matthew J.; Canister, Tracy Q.; Chow, Benjamin; Dunning, Allison; Al-Mallah, Mouaz H.; Cademartiri, Filippo; et al. (European Heart Journal - Cardiovascular Imaging, 2017)
Background: Left ventricular (LV) volumetric and functional parameters measured with cardiac computed tomography (cardiac CT) augment risk prediction and discrimination for future mortality. Gender- and age-specific standard values for LV dimensions and systolic function obtained by 64-slice cardiac CT are lacking. Methods and results: 1155 patients from the Coronary CT Angiography EvaluatioN For Clinical Outcomes: An InteRnational Multicenter registry (54.5% males, mean age 53.1 ± 12.4 years, range: 18-92 years) without known coronary artery disease (CAD), structural heart disease, diabetes, or hypertension who underwent cardiac CT for various indications were categorized according to age and sex. A cardiac CT data acquisition protocol was used that allowed volumetric measuring of LV function. Image interpretation was performed at each site. Patients with significant CAD (>50% stenosis) on cardiac CT were excluded from the analysis. Overall, mean left ventricular ejection fraction (LVEF) was higher in women when compared with men (66.6 ± 7.7% vs. 64.6 ± 8.1%, P < 0.001). This gender-difference in overall LVEF was caused by a significantly higher LVEF in women ≥70 years when compared with men ≥70 years (69.95 ± 8.89% vs. 65.50 ± 9.42%, P = 0.004). Accordingly, a significant increase in LVEF was observed with age (P = 0.005 for males and P < 0.001 for females), which was more pronounced in females (5.21%) than in males (2.6%). LV end-diastolic volume decreased in females from 122.48 ± 27.87 (<40 years) to 95.56 ± 23.17 (>70 years; P < 0.001) and in males from 155.22 ± 35.07 (<40 years) to 130.26 ± 27.18 (>70 years; P < 0.001). Conclusion: Our findings indicate that the LV undergoes a lifelong remodelling and highlight the need for age and gender adjusted reference values.
EVALuna2:33622